A Comparative Review of Iran and Germany Tenth Grade English Textbook - Aramreza Sadeghi (مطالعات زبانی و بلاغی)
The purpose of the present study is to analyze the content of the 10th grade English textbook based on educational goals and to compare it with the similar basic English textbook in Germany. The study is an applied one and its research method is descriptive and content analysis. The results show that 10th grade English books in Iran are mostly based on learning through the analysis of language components such as grammar, vocabulary, and reading skills, and the authors of the book have paid less attention to practical aspects such as conversation and practice. By analytical comparison of the Iranian book with the German book it was found that the culture of the target language should be addressed, texts and exercises should be more varied, and more attention should be paid to economize on the of paper. The findings of this study can assist policy makers as well as material developers in providing appropriate content in language teaching textbooks.